Telehealth in cancer care: during and beyond the COVID‐19 pandemic. Issue 1 (11th February 2021) - Burbury, Kate; Wong, Zee‐Wan; Yip, Desmond; Thomas, Huw; Brooks, Peter; Gilham, Leslie; Piper, Amanda; Solo, Ilana; Underhill, Craig
Abstract: The COVID‐19 pandemic has precipitated the rapid uptake of telehealth in cancer care and in other fields. Many of the changes made in routine clinical practice could be embedded beyond the duration of the pandemic. This is intended as a practical guide to cancer clinicians and others in establishing and improving the quality of consultations performed by telehealth.